Maternal and Perinatal Outcomes in Teenage Versus Adult Pregnancies – A Prospective Comparative Study - Prathima S; Sarojini -; Ashakiran T R; Manasa K; Bhanu BT (RGUHS Journal of Medical Sciences)
Objectives To assess maternal and neonatal outcomes in teenage versus adult pregnant women and also to compare the sociodemographic characteristics of these women.Methods It was a cross-sectional study conducted at Bangalore Medical College and Research Institute in which 1368 teenage pregnant women and 15605 adult pregnant women were studied for a period of 12 months. Maternal parameters such as sociodemographic details education status parity antenatal complications postpartum complications and mode of delivery were compared. Neonatal parameters compared included gestational age at birth birth weight need for resuscitation neonatal intensive care unit NICU admission and perinatal death.Results The percentage of teenage pregnancies was 8.05. Majority of women in the teenage group were from rural background 68.56 had only primary education 76.68 were primiparous 95 had lesser antenatal visits 52.26 with late initiation of first antenatal visit in second trimester 6505. The occurrence of anaemia 6 hypertensive disorders 17.25 low birth weight 30.26 NICU admissions 24 and perinatal deaths 2.5 was greater in teenage group P value-lt0.0001. Significant differences were noted between the two studied groups regarding sociodemographic characteristics pattern of antenatal care antenatal complications hypertensive disorders of pregnancy and anaemia and neonatal outcomes.Conclusion Teenage pregnancy was found linked to high incidence of maternal and neonatal complications. Maternal and perinatal morbidity and mortality can be minimized in teenage pregnancies by providing education improving their nutritional status socioeconomic status educating them about contraception safe sex practices to avoid unintended pregnancies and by providing them good antenatal care.